Wearable microfluidic biosensors with haptic feedback for continuous monitoring of hydration biomarkers in workers - Julia C. Spinelli; Brandon J. Suleski; Donald E. Wright; Joseph L. Grow; Gabriel R. Fagans; Maura J. Buckley; Da Som Yang; Kaitao Yang; Steven M. Beil; Jessica C. Wallace; Thomas S. DiZoglio; Jeffrey B. Model; et al. (npj Digital Medicine)
Abstract Real-time monitoring of hydration biomarkers in tandem with biophysical markers can offer valuable physiological insights about heat stress and related thermoregulatory response. These metrics have been challenging to achieve with wearable sensors. Here we present a closed-loop electrochemical/biophysical wearable sensing device and algorithms that directly measure whole-body sweat loss, sweating rate, sodium concentration, and sodium loss with electrode arrays embedded in a microfluidic channel. The device contains two temperature sensors for skin temperature and thermal flux recordings, and an accelerometer for real-time monitoring of activity level. An onboard haptic module enables vibratory feedback cues to the wearer once critical sweat loss thresholds are reached. Data is stored onboard in memory and autonomously transmitted via Bluetooth to a smartphone and cloud portal. Field studies conducted in physically demanding activities demonstrate the key capabilities of this platform to inform hydration interventions in highly challenging real-world settings.